Community Based Tourism in The Management of Tourism in Jati Larangan and Sengon Park - Deni Dwi Ananti; Fitri Puji Lestari; Hesti Purwaningrum; Halim Ahmad (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The people of Iroyudan have organize the Jati Larangan and Sengon areas so that their function is no longer limited to being an area that has cultural historical value, but also has economic value by making it a tourist attraction. This study uses descriptive research with a qualitative approach. The theoretical basis used is the ASEAN standard community-based tourism management concept. The management of tourism through two existing tourist objects, namely Jati Larangan and Taman Sengon, has shown a fairly massive community involvement starting from planning, development, to its current management. The community is also consciously willing to prioritize common interests over individual interests. Tourism activities in Iroyudan to be well organized, so that people can begin to feel the benefits of tourism activities in their hamlet.